Prevalence of Anemia Among University Students; Tarhuna, Libya (Derna Academy Journal for Applied Sciences, 2025)
Background: Anemia is a prevalent condition affecting red blood cells and hemoglobin, leading to oxygen deficiency in the body's tissues. This study aimed to investigate anemia prevalence among university students, its associated factors, and the impact on their health and academic performance.  Methods: A cross-sectional survey was conducted on 100 university students from different collees of Azzaytuna University the  age between 18-24 years; blood samples were collected to measure hemoglobin, red blood corpuscular count, and hematocrit levels. A questionnaire was designed to collect data about the volunteers, including dietary habits, medical history, and anemia symptoms. Results: The study revealed that 29% of studied students were anemic (27% Mild anemia, while 2% severe). Correlations between hemoglobin, red blood corpusculs count, and hematocrit highlighted the need for comprehensive health assessments. Weight distribution indicated potential nutritional deficiencies. Self-reported data showed 25% of students had anemia, with fatigue (62%), dizziness (44%), and accelerated heartbeat (41%) as common symptoms. Only 9% of students received treatment, and 31% had medical examinations. The results align with previous studies, indicating higher anemia prevalence among female students. The study emphasizes the impact of anemia on student health and the need for targeted interventions. Regional variations in anemia prevalence highlight the influence of demographic and cultural factors.  Conclusion: anemia is a significant concern among university students, particularly females. Comprehensive health assessments, nutritional education, and early detection programs are essential to address this issue. Further research is needed to develop effective interventions and improve student health services